2018
DOI: 10.1093/mnras/sty1841
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the measurement accuracy of pre-atmosphere velocities of meteoroids

Abstract: Many existing optical meteor trajectory estimation methods use the approximation that the velocity of the meteor at the beginning of its luminous phase is equivalent to its velocity before atmospheric entry. Meteoroid kinetic energy loss prior to the luminous phase cannot be measured, but for some masses and entry geometries neglecting this loss may lead to non-negligible deceleration prior to thermal ablation. Using a numerical meteoroid ablation model, we simulate the kinematics of meteoroids beginning at 18… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…At the end of the luminous path, 21.5 km above the ground, the meteoroid slowed down to 4.0 ± 0.2 km s -1 . The estimated value of 76 km for the beginning height of the observed trajectory is in close agreement with experimental and simulated data presented in Vida et al (2018) for fireballs of asteroidal origin with a low entry speed (<13 km s -1 ), as seen by low sensitivity all-sky systems. They also found that low velocity meteors decelerate significantly prior to detection of the visible meteor trail.…”
Section: Atmospheric Trajectory and Dynamical Modelsupporting
confidence: 88%
“…At the end of the luminous path, 21.5 km above the ground, the meteoroid slowed down to 4.0 ± 0.2 km s -1 . The estimated value of 76 km for the beginning height of the observed trajectory is in close agreement with experimental and simulated data presented in Vida et al (2018) for fireballs of asteroidal origin with a low entry speed (<13 km s -1 ), as seen by low sensitivity all-sky systems. They also found that low velocity meteors decelerate significantly prior to detection of the visible meteor trail.…”
Section: Atmospheric Trajectory and Dynamical Modelsupporting
confidence: 88%
“…As the atmospheric correction to the initial velocity vector (Pecina and Ceplecha , ) used in C‐87 is not always applied (Vida et al. ), we shall additionally provide the orbital results of C‐87 by equating v ∞ and v 0 (see the Methods section) to assess the effects.…”
Section: Resultsmentioning
confidence: 99%
“…We must also note that the determination of the pre‐atmospheric velocity, v ∞ , as outlined in the appendix of Pecina and Ceplecha (), is not as well known among the meteor modeling community, and is frequently mistaken as the velocity at the first triangulated point, v 0 (Vida et al. ). This will lead to a misuse of Equations and in calculating v g as the Earth's atmospheric influence will not be accounted for.…”
Section: Methodsmentioning
confidence: 99%
“…Triangulation During the analysis of the event detected by the DFN, two separate triangulation methods were used. We did this to check the sensitivity of the orbital history for this meteoroid to the triangulation method based on the work of previous studies [Vida et al, 2018]. Our primary method is a straight line least squares (SLLS) algorithm, modified from [Borovicka, 1990], with an Extended Kalman Smoother (EKS) for velocity determination [Sansom et al, 2015].…”
Section: Event Dn160822_03 Observationsmentioning
confidence: 99%